Določitev spola anglizmov v slovenščini - Sicherl, Eva (Slavistična revija, 2019)
This article focuses on principles governing the assignment of gender when English lexemes are borrowed into Slovene. In the transfer from a natural-gender language system (English) into a grammatical-gender language system (Slovene), natural gender is usually retained in animate nouns, while in inanimate nouns gender is assigned following somewhat different criteria.
Keywords: angleščina; Anglicisms; anglizmi; določitev spola; English language; gender assignment; jezikovni stik; language contact; Slovenian language; slovenščina